Thermal history of the giant Qulong Cu–Mo deposit, Gangdese metallogenic belt, Tibet: Constraints on magmatic–hydrothermal evolution and exhumation - Zhao, Junxing; Qin, Kezhang; Xiao, Bo; McInnes, Brent; Li, Guangming; Evans, Noreen; Cao, Mingjian; Li, Jinxiang (Gondwana research, 2016)
A complete thermal history for the Qulong porphyry Cu–Mo deposit, Tibet is presented. Zircon U–Pb geochronology indicates that the mineralization at Qulong resulted from brecciation-veining events associated with the emplacement of a series of intermediate-felsic intrusions. Combined with previously published ages, our results reveal a whole intrusive history of the Qulong composite pluton. Causative porphyries were emplaced at ~16.0Ma as revealed by 40Ar–39Ar dating of hydrothermal biotite (15.7±0.2Ma) and sericite (15.7±0.2Ma). Zircon and apatite (U–Th)/He (ZHe and AHe) dating of Qulong revealed that both followed similar, monotonic thermal trajectories from 900°C (U–Pb ages: 17.5–15.9Ma) to 200°C (ZHe: 15.7–14.0Ma), and that the causative porphyries experienced faster cooling at a maximum rate of greater than 200°C/myr. The Qulong deposit was exhumed between 13.6Ma and 12.4Ma (AHe) at an estimated rate of 0.16–0.24mm/y, which is consistent with previous estimates for other Gangdese Miocene porphyry deposits. Our AHe thermochronology results suggest that neither the Gangdese thrust system, nor the Yadong–Gulu graben affected or accelerated exhumation at the Qulong deposit. [Display omitted] •The first paired ZHe and AHe thermochronological investigations at Qulong.•Hypogene processes happened during ~1Ma at a high cooling rate of over 200°C/myr.•The Qulong deposit began to be exhumed from 13.6–12.4Ma at rate of 0.16–0.24mm/y.